Effect of sustained loading and environmental conditions on the creep behavior of an epoxy adhesive for concrete structures strengthened with CFRP laminates. (15th November 2017) - Emara, M.; Torres, L.; Baena, M.; Barris, C.; Moawad, M.
Abstract: In this paper, the creep behavior of a structural epoxy adhesive used for strengthening Reinforced Concrete (RC) structures with Carbon Fiber Reinforced Polymer (CFRP) laminates is studied through an experimental program. Long-term tensile creep tests were carried out inside a climate chamber using sustained loading levels, temperature and humidity as the parameters for the study. The specimens were kept loaded inside the climate chamber for 1000 h. Standard Tensile Tests (STT), Dynamic Mechanical Analysis (DMA) and Differential Scanning Calorimetry (DSC) tests were carried out to characterize the adhesive used. In general, the results obtained revealed that changing temperature and humidity conditions greatly affect not only instantaneous and creep strain values, but also time to failure, leading to a change in the overall behavior of the adhesive.